The Microbiome and Gut Endocannabinoid System in the Regulation of Stress Responses and Metabolism - Srivastava, Raj Kamal; Lutz, Beat; Ruiz de Azua, Inigo (Frontiers in Cellular Neuroscience, 2022)
The endocannabinoid system, with its receptors and ligands, is present in the gut epithelium and enteroendocrine cells, and is able to modulate brain functions, both indirectly through circulating gut-derived factors and directly through the vagus nerve, finally acting on the brain’s mechanisms regarding metabolism and behavior. The gut endocannabinoid system also regulates gut motility, permeability, and inflammatory responses. Furthermore, microbiota composition has been shown to influence the activity of the endocannabinoid system. This review examines the interaction between microbiota, intestinal endocannabinoid system, metabolism, and stress responses. We hypothesize that the crosstalk between microbiota and intestinal endocannabinoid system has a prominent role in stress-induced changes in gut-brain axis affecting metabolic and mental health. Inter-individual differences are commonly observed in stress responses, but mechanisms underlying resilience and vulnerability to stress are far from understood. Both gut microbiota and the endocannabinoid system have been implicated in stress resilience. We also discuss interventions targeting the microbiota and the endocannabinoid system to mitigate metabolic and stress-related disorders.